CHARACTERISTICS BEHAVIOR OF PARTIALLY REPLACED CEMENT WITH KANKARA METAKAOLIN IN CONCRETE PRODUCTION (FUDMA JOURNAL OF SCIENCES, 2022)
Cement which is the basic constituent of concrete is posing a global threat through its adverse effects on environment during its production processes. It has become very popular that in the production of 1ton of cement, 1ton of CO2 is released into the atmosphere which causes greenhouse emission and global warming through. It has therefore become imminent to have alternative materials that will be readily available, ecofriendly and not to compromised strength and with required durability to replace conventional cement. In this research work, calcined kaolin obtained from Kankara Local Government of Katsina State was used to replace cement at 5%, 10%, 15%, 20% and 25% respectively. Oxide composition test, slump test, compressive strength test and Split Tensile strength test were carried out for both control and concrete produced with metakaolin as partial replacement of cement. It was noticed that the metakaolin was of class N Pozzolan and having a good compressive and tensile strengths that surpassed that of the control concrete mix. From test results it was concluded that cement can be replaced by metakaolin at 20% replacement to achieve a sustainable concrete with good strength and durability. One of the setbacks that was noticed is that the percentage increase of metakaolin in the concrete decrease the workability of the concrete and has to be compensated by adding super plasticizer. Also, even though kaolin is available in some parts of the country,
Keywords: Cement, calcined kaolin, metakaolin